The culture and development manifesto - Klitgaard, Robert E. (Oxford University Press, 2021)
This book is a manifesto for building on diverse cultural strengths in international development. Gently but firmly, it demonstrates how and why cultural studies and anthropology have fallen short in application-and, arguably, in terms of social science. Nonetheless, anthropology and cultural studies have much to offer, as the book shows through lively examples ranging from West Africa to South Sudan, from Haïti to Hawai'i, from Nepal to Native America. Anthropology can provide distinctive information and compelling descriptions, case studies of successful adaptation and resistance, the deconstruction of cultural texts, useful checklists, and processes for combining outside expertise and local knowledge. Beyond the important task of identifying how cultural features interact with particular projects, The Culture and Development Manifesto displays new ways to think about goals (and risks), new kinds of alternatives, new and perhaps métisse ways to implement, and, as a result, new kinds of politics.